Use of UHPH to Obtain Juices With Better Nutritional Quality and Healthier Wines With Low Levels of SO2 - Morata, Antonio; Guamis, Buenaventura (Frontiers in Nutrition, 2020)
Ultra-high pressure homogenization (UHPH) is a high pressure technique in which a fluid is pressurized by pumping at higher than 200MPa and instantaneously depressurized at atmospheric pressure across a special valve. Full process takes lower than 0.2 seconds and the in-valve time is lower than 0.02 seconds. In valve extremely intense impacts and shear forces produce the nanofragmentation of whatever biological tissue at a range of 100-300nm. The antimicrobial effect is highly effective reaching easily inactivation levels higher than 6-log cycles even at low in-valve temperatures. At in-valve temperatures of 140-150ºC (0.02 seconds) is possible the destruction of thermoresistant spores. Even when the temperature in-valve can be elevated (70-150ºC), can be considered a gentle technology because of the tremendously short processing time. It is easy to get outlet temperatures after valve of 20-25ºC by the expansion and assisted by heat exchangers. Thermal markers as hydroxymethylfurfural (HMF) are not formed neither deleterious effects are observed in sensitive compounds as terpenes or anthocyanins. Probably because of the low effect in covalent bonds of small molecules of the high-pressure techniques compared with thermal technologies. Additionally, intense inactivation of oxidative enzymes is observed, therefore protecting the sensory and nutritional quality of fruit juices and avoiding or reducing the use of antioxidants as sulphites. Therefore, UHPH can be consider a powerful and highly effective continuous and sterilizing technology without thermal repercussions, able to keep fresh juices with most of their initial sensory and nutritional quality and allowing high quality and natural fermented derivatives as wine.